Perceptions of Physicians and Allied Health Care Workers of Pharmacists’ Role In Care Optimization for Schizophrenic Patients At Federal Neuro-Psychiatric Hospital Maiduguri, North-Eastern Nigeria - Yusuf, H; Giwa, A; Mohammed, S; Abdu, SN Aguye; Dungus, FM; Sani, A; Ashemi, F (Bangladesh Journal of Medicine, 2019)
Introduction: In clinical practice, it is required that a profession not only clearly describe their own roles and responsibilities to other professionals but should also be aware of other professions’ roles in relation to their own. The objective of this study was to assess the perceptions of physicians and allied health care workers (Other health care professionals) of the roles of pharmacists in optimizing care for schizophrenic patients. Methods: A self-administered 17-item validated questionnaire was distributed to 120 health care professionals working at Federal Neuro-Psychiatric Hospital Maiduguri from September to October 2016. Results obtained were analysed using Chi-square test. Results: Health care professionals mostly had positive perceptions with a statistically significant difference (P< 0.05) across all assessed items. However, competent and knowledge of the pharmacists accounting for 93 (83.8%), involvement of the pharmacist in patient care accounting for 91(82%) and reassuring patients to improve quality of life accounting for 98(88.3%) had the highest number of health care professionals with positive perceptions while documenting patient care, monitoring and reemphasizing physicians instructions had the lowest accounting for 69 (62.2%), 74(66.7%) and 74 (66.7%) respectively in the different sections. Conclusions: The health care professionals surveyed mostly had positive perceptions. Thus, pharmacists can leverage on this to meet their roles in optimizing care for schizophrenic patients. Bangladesh J Medicine Jan 2019; 30(1) : 19-23